Time-motion characteristics of match-play in elite Polish youth soccer players of various playing positions - Dolanski, B.; Rompa, P.; Hongyou, L.; Wasielewski, K.; Szwarc, A. (Baltic Journal of Health and Physical Activity, 2018)
Background: The aim of this study is to examine and compare the distance covered with high-intensity running and to determine differences in maximum velocities achieved in a match by 15-19-year-old elite Polish soccer players depending on their age and playing positions.